Asymmetric induction in the addition of enantiomerically pure H-phosphinate to chiral aldimines: diastereoselective generation of α-amino phosphinates with P, C-stereogenic centers. Issue 17 (1st October 2016) - Yang, Meng; Xu, Hao; Zhou, Zhong-Yang; Zhang, He; Liu, Li-Juan; Sun, Yong-Ming; Nie, Shao-Zhen; Zhao, Chang-Qiu
Graphical abstract: Abstract: α-Amino phosphinates with P, C -stereogenic centers were prepared from a P -retained addition of ( R P )-(−)-menthyl H -phenylphosphinate to ( R )-aldimines with up to 86:14 dr under catalyst and solvent free condition at ambient temperature; the single ( S P, S α-C )-stereoisomers were isolated in moderate yields. Chirality on the nitrogen of chiral aldimine was proposed to control the stereoselectivity, and the (−)-menthoxyl showed mismatched asymmetric induction with ( S )-aldimines.